Drug utilization pattern and cost estimates of antihypertensive drugs in pharmacies BPJS Kesehatan back-referral program in Kudus Regency - Wildayanti; Tri Wijayanti; Tri Murti Andayani (Universitas Islam Indonesia, 2023)
AbstractBackground: Hypertension is one of the main causes of mortality and morbidity in Indonesia. Drug usage, utilization patterns, and cost estimates are important elements in calculating drug needs in the forecasting of drug needs plans for pharmacies.Objective: to determine the pattern of drug use with the Anatomical Therapeuetik Chemical (ATC)/Defined Daily Dose (DDD) and Drug Use 90% (DU90%) methods and the estimated cost of antihypertensives with the use of antihypertensive drugs based on the national formulary.Methods: This research uses observational methods using a cross-sectional design. Retrospective data collection includes prescription from BPJS Kesehatan back-referral program (PRB) which goes into pharmacy A, B, and C for the period 2020.Results: The most widely used drugs at pharmacy A, B and C based on ATC/DDD classification were amlodipine, candesartan, ramipril, hydrochlorothiazide, and lisinopril. Amlodipine was the most frequent drug in the DU segment 90%. The highest cost of using the drug was candesartan 16 mg (Rp 4,381,531). The percentages of adherence to the use of antihypertensive drugs with the national formulary in pharmacy A, B, and C were 73.91%, 80%, and 68.42%, respectively.Conclusion: In general, the highest consumption of antihypertensive drugs in Back-Referral Program (PRB) pharmacies in the area of Kudus Regency, which is included in the DU segment 90%, was amlodipine, and the suitability of drugs with the National Formulary has not reached 100%. Referring to the results of the pattern of use of PRB drugs in this study, it is hoped that there will be better coordination between BPJS Kesehatan and pharmacies regarding the distribution and availability of PRB drugs.Keywords: ATC/DDD, DU 90%, hypertension, national formulary, PRB IntisariLatar belakang: Hipertensi merupakan salah satu penyebab utama mortalitas dan morbiditas di Indonesia. Pola pemakaian obat dan perkiraan biaya merupakan elemen penting dalam menghitung rencana kebutuhan obat di apotek. Tujuan: Penelitian ini bertujuan untuk mengetahui pola penggunaan obat dengan metode Anatomical Therapeuetik Chemical (ATC)/ Defined Daily Dose (DDD), DU 90%, perkiraan biaya antihipertensi dan kesesuaian penggunaan obat antihipertensi dengan Formularium Nasional (Fornas).Metode: Penelitian menggunakan metode observasional dengan desain cross sectional. Pengumpulan data dilakukan secara retrospektif meliputi resep Program Rujuk Balik (PRB) yang masuk ke apotek A, B dan C pada periode 2020.Hasil: Penggunaan obat di apotek A, B dan C berdasarkan ATC/DDD yang banyak digunakan yaitu amlodipin, candesartan, ramipril, hidroklorotiazid dan lisinopril. Segmen DU 90% penggunaan obat tertinggi adalah amlodipin dan biaya penggunaan obat tertinggi yaitu candesartan 16mg sebesar Rp4.381.531,00. Persentase kesesuaian penggunaan obat antihipertensi dengan Fornas pada apotek A, B, dan C yaitu 73,91%, 80%, dan 68,42%. Kesimpulan: Secara umum konsumsi obat antihipertensi terbanyak di apotek PRB Kabupaten Kudus yang masuk dalam segmen DU 90% adalah amlodipin serta kesesuaian obat dengan Fornas belum mencapai 100%. Merujuk pada hasil pola penggunaan obat PRB pada penelitian ini, diharapkan adanya koordinasi yang lebih baik antara BPJS Kesehatan dengan pihak apotek mengenai distribusi dan ketersediaan obat PRB.Kata kunci: ATC/DDD, DU 90%, hipertensi, formularium nasional, PRB